Mechanistic Studies of Inactivation of Inducible Nitric Oxide Synthase by Amidines - Tang, Wei (Biochemistry, 2015)
Nitric oxide synthase (NOS) catalyzes the conversion of l-arginine to l-citrulline and nitric oxide. N(5)-(1-Iminoethyl)-L-ornithine (L-NIO), an amidine-containing molecule, is a natural product known to be an inactivator of inducible NOS (iNOS). Because of the presence of the amidine methyl group in place of the guanidine amino group of substrate l-arginine, the active site heme peroxy intermediate sometimes cannot be protonated, thereby preventing its conversion to the heme oxo intermediate; instead, a heme oxygenase type mechanism occurs, leading to conversion of the heme to biliverdin. This might be a new and general inactivation mechanism for heme-containing enzymes. In the studies described here, we attempted to provide support for amidines as substrates and inactivators of iNOS by the design and synthesis of amidine analogues of l-NIO having groups other than the amidine methyl group. No nitric oxide or enzyme-catalyzed products could be detected by incubation of these amidines with iNOS. Although none of the l-NIO analogues acted as substrates, they all inhibited iNOS; increased inhibitory potency correlated with decreased substituent size. Computer modeling and molecular dynamics simulations were run on 10 and 11 to rationalize why these compounds do not act as substrates. Unlike the methyl amidine (L-NIO), the other alkyl groups block O(2) binding at the heme iron. Compounds 8, 9, and 11 were inactivators, but no heme was lost and no biliverdin was formed. No kinetic isotope effect on inactivation was observed with perdeuterated ethyl 8. A small amount of dimer disruption occurred by these inactivators, although the amount would not account for complete enzyme inactivation. The l-NIO analogues inactivate iNOS by a yet unknown mechanism, but it is different from that of l-NIO, and the inactivation mechanism previously reported for l-NIO appears to be unique to methyl amidines.